Moralismo e política: o papel da FIESP na política brasileira - Couto, Pedro Santiago (2019)
This paper analyzes the role of the federation of são paulo industries (FIESP) in Lula and Dilma governments. It aimed to understand the constitution of the relationship between moralism and politics from fiesp‘s role in the political decisions of those governments by historicizing the justifications for support at crucial moments and, subsequently, the disruption and financing of publicity campaigns to convince public opinion about the fight against corruption that acted in the consolidation of the 2016 coup d‘etat, the work relates moral values and class interests in recent brazilian politics.